PROBLEMATIKA PENUTUR NON ARAB DALAM PEMBELAJARAN BAHASA ARAB - Udin Zaenudin; Wafiq Ropiatul Munawaroh (HASBUNA : Jurnal Pendidikan Islam, 2023)
In Indonesia, the problem of learning Arabic for non-Arabs seems to have never been resolved, eventhough there have been many Arabic learning methods written by Arabic language experts. This problem is reflected in the fact that there are still many students who still find it difficult to master Arabic, and it takes a long time to master the four skills of Arabic. The purpose of the study is to find problems and difficulties faced by Arabic learners and then try to find the factors that cause the problems so that it is easy to make efforts to overcome these factors, as well as to make it easier for non-Arabic learners to master the 4 language skills. Secondary data was collected from secondary sources such as books or writings related to the research object, including the Indonesian Language Dictionary and other books. The result is that in learning Arabic, students are faced with problems that non-Arab learners cannot avoid, namely linguistic and non-linguistic problems. To get through it, the learner must pay attention to these problems and other factors that cause problems by paying attention to the following things; improving the quality of teachers, providing motivation to students, selecting appropriate learning methods, forming a language environment and sustainable evaluation.